Pharmacokinetics of Photogem Using Fluorescence Spectroscopy in Dimethylhydrazine-Induced Murine Colorectal Carcinoma - Raduan Hage; Juliana Ferreira; Vanderlei Salvador Bagnato; José Dirceu Vollet-Filho; Hélio Plapler (International Journal of Photoenergy)
This study aimed to investigate the pharmacokinetics of a hematoporphyrin derivative in colonic tumors induced by dimethylhydrazine and adjacent normal colon in Wistar rats using an in vivo fluorescence spectroscopy technique. In conventional clinical application of photodynamic therapy, the interval between photosensitizer (PS) administration and lesion illumination is often standardized without taking into account variations due to the type or localization of the tumor and intrinsic differences in the microcirculation and vascular permeability of each target organ. The analysis of the fluorescence spectra was based on the intensity of porphyrin emission band centered at around 620 nm in normal colon and colon tumors. The photosensitizer fluorescence intensity rapidly grew for carcinoma and normal colon, reaching the maximum values 1 and 3 hours after PS injection, respectively. Data presented here allow us to verify that the best compromise between selectivity and drug concentration for colon carcinoma in rats took place in the interval between 1 to 4 h after PS injection.